Using the Song Maker Feature on Chrome Music Lab as a Music Learning Media - Dwi Utami Ningsih; Yudi Sukmayadi (Yayasan Keluarga Guru Mandiri, 2023)
This study aims to reveal how to use the Song Maker feature in Chrome Music Lab as a medium that can be used in remote music learning. Data collection was taken from reference books and journals, as well as YouTube and Google applications. The research method used was Research and Development (RD) with the Waterfall development model. The resulting product is in the form of a learning video that contains an introduction to Chrome Music Lab and the Song Maker feature, how to access and the process of making songs in the Song Maker feature. The results of the development of the Song Maker feature in Chrome Music Lab show that the feature is very easy, useful, and fun to use as learning media. The test results show that the product is ready to use because the respondents are satisfied. Chrome's Music Lab, specifically the Song Maker feature, provides an alternative for educators to extrapolate music education barriers by connecting active methods with technological, digital experiences for distance learning. The implication of the finding is using the Song Maker feature of Chrome Music Lab as a media for learning music can be used in the classroom for music creation lessons.